2021
DOI: 10.1039/d1ra06233f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel DNA aptamer that selectively targets lung cancer serum

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Different from secretome SELEX, serum-SELEX needs to link serum proteins to a carboxylate-modified magnetic bead for the separation of unbound sequences. In the report of Zhao et al, CLEC3B was identified as the target protein by MALDI-TOF MS and secondary peptide sequencing MS analysis [ 118 ]. In addition, the ELISA confirmed the overexpression of CLEC3B in lung cancer patients, which makes it useful in the diagnosis [ 119 ].…”
Section: The Application Of Aptamer-based Biomarker Discovery In Vari...mentioning
confidence: 99%
“…Different from secretome SELEX, serum-SELEX needs to link serum proteins to a carboxylate-modified magnetic bead for the separation of unbound sequences. In the report of Zhao et al, CLEC3B was identified as the target protein by MALDI-TOF MS and secondary peptide sequencing MS analysis [ 118 ]. In addition, the ELISA confirmed the overexpression of CLEC3B in lung cancer patients, which makes it useful in the diagnosis [ 119 ].…”
Section: The Application Of Aptamer-based Biomarker Discovery In Vari...mentioning
confidence: 99%
“…Thus, aptamers with improved specificity and selectivity can be obtained for diagnostic application. For example, Apt-5 can bind to human CLEC3b, which plays an important role in infection, inflammation, and tumor immunity [73,74]. Aptamer Apt-5 can be used as a molecular probe to detect lung cancer.…”
Section: Serum-selexmentioning
confidence: 99%
“…Aptamers (single-stranded DNA or RNA) have been proven to be a powerful tool for biomarker discovery. Several researchers have employed aptamers to discover biomarkers in various diseases such as lung cancer [8], leukemias [9], ovarian cancer [10,11], and Chagas disease [12], among many others. However, it is evident that the SELEX strategies utilized in these studies exhibit notable diversity, highlighting the absence of a standardized protocol for biomarker discovery from biological samples.…”
Section: Introductionmentioning
confidence: 99%